(untitled) (Damascus University Journal of agriculture sciences, 2021)
The aim of the research is to study the effect of vacuum packing in increasing the duration of conservation the sausages produced from the fish "Chalf". The sausages were manufactured in the meat laboratory at the Department of Food Science at the Faculty of Agriculture in Damascus, in accordance with the general reference steps adopted in principle. The samples were divided into two sections at a rate of 100 g of ready-to-eat sausages, which were kept in bags of polyethylene under vacuum. The other part is normal storage. The research was carried out between 9/2017 and 2/2018. To investigate the objective, the chemical changes (total volatile basic nitrogen, thiobarbituric acid), microbial (total count, psychrotrophic bacteria, lactic acid bacteria, yeast and molds, staphylococcus aureus, coliforms, and E. coli) were studied during conservation at 3-5 °CThe microbial flora of the sausages comprised mainly mesophilic bacteria, psychrotrophic bacteria, lactic acid bacteria, yeast and molds. No coliform, staphylococcus, and coliform bacteria were observed.. The values ​​of total volatile basic nitrogen and thiobarbituric acid increased gradually with conservation time.